PENGARUH KEWAJIBAN MORAL, SOSIALISASI PERPAJAKAN, DAN KUALITAS PELAYANAN TERHADAP KEPATUHAN WAJIB PAJAK KENDARAAN BERMOTOR - Ni Wayan Intan Rismayanti (UNHI Press, 2021)
Vehicles are a must have reqvirement, it’s because it capable of supporting the community activities. Both of vehicle purchases level and the development of the automotive world are increasing. The more people who own the vehicles cause the number of vehicle taxpayer increase every year. However, the tax collection still needs to be improved considering that there are many people who aren’t obedient in paying the taxes. We can see there are evidenced by the existence of tax arreas. This study, aimed is to know the influence of moral obligations, tax socialization, and service quality of vehicle taxpayer compliance. The population of this study were all vehicle taxpayers in Tabanan regency. The sample of the study was 100 respondents that obtained the slovin form. This used accidental sampling technique. The data collected by spread out a questionnaire, and then analyzed using multiple linear regression test. This study showed; simultaneously, a moral obligation tax socialization and service quality have influenced to vehicle taxpayer compliance. Partially, it showed moral obligations have a positive significant’s affect to taxpayer compliance, while tax socialization and service quality didn’t affect to vehicle taxpayer compliance.